Human Umbilical Cord-Derived Mesenchymal Stem Cells Alleviate Acute Lung Injury Caused by Severe Burn via Secreting TSG-6 and Inhibiting Inflammatory Response - Xiaohong Hu; Lingying Liu; Yu Wang; Yonghui Yu; Zhongyuan Li; Yanan Liu; Jiake Chai (Stem Cells International)
Objectives. To investigate whether hUC-MSCs attenuated severe burn-induced ALI and the effects were based on TSG-6 secreted from hUC-MSCs. Method. A rat model was established and evaluated as follows: cytokine expression was measured by ELISA, and both inflammatory cell infiltration and lung injury were assessed by immunohistochemistry assay. Results. In vitro, TSG-6 levels in serum from the burn group were significantly increased compared with those from the sham group. In vivo, TSG-6 levels of lung tissues and serum in the burn+hUC-MSC group were significantly increased compared with those in the burn group. Both in lung tissues and in serum, increased levels of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) were remarkably decreased, but the anti-inflammatory cytokine IL-10 increased after hUC-MSC administration (p<0.05). These significant positive effects after hUC-MSC transplantation did not occur in the burn+siTSG-6 group. Conclusion. The intratracheal implantation of hUC-MSCs has been an effective treatment for severe burn-induced ALI via promoting TSG-6 secretion and inhibiting inflammatory reaction in lung tissue.